2010
DOI: 10.30707/jste47.2kelley
|View full text |Cite
|
Sign up to set email alerts
|

Two Approaches to Engineering Design: Observations in sTEm Education

Abstract: A comparative study was conducted to compare two approaches to engineering design curriculum across different schools (inter-school) and across two curricula Project Lead the Way and Engineering Projects in Community Service (inter-curricula). The researchers collected curricula material including handouts, lesson plans, guides, presentation files, design descriptions, problem statements, and support guides. The researchers conducted observations in the classrooms to collect qualitative indicators of engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Commonly, the literature suggests that these capabilities are best developed through STEM education practices that use real world contexts and present learners with authentic problems or projects to work upon (e.g. Hefty, 2015; Kelley et al., 2010; Redmond et al., 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Commonly, the literature suggests that these capabilities are best developed through STEM education practices that use real world contexts and present learners with authentic problems or projects to work upon (e.g. Hefty, 2015; Kelley et al., 2010; Redmond et al., 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students in these types of programs complete a series of program specific pre‐engineering courses with corresponding laboratory experiences, in conjunction with their general academic curriculum, to prepare them for post‐secondary success in this specific field (Lynch, Peters‐Burton, & Ford, ). In a review of engineering curriculum programs, Kelley, Brenner, and Pieper () found that EOPs were effective in helping students develop problem‐solving abilities. Silk et al () posited that design science programs such as these encourage students to be active learners who are responsible for creating and evaluating ideas and designs while gaining feedback from peers and the classroom community via justifying rationale and explanations from their inquiry.…”
Section: Four Approaches To Stem Educationmentioning
confidence: 99%
“…For example, Kelley et al (2010) found that even among students who had completed advanced courses in mathematics, very little mathematics was employed to solve problems during the design process. In addition, Taraban et al (2007) noted that many engineering students lacked the flexibility to apply higher-order thinking skills and continued to use low-level conceptual knowledge to solve problems.…”
Section: Introductionmentioning
confidence: 98%